Causes of mortality in a department of cardiology over a 15-year period. (February 2021) - Karkabi, Basheer; Khoury, Razi; Zafrir, Barak; Jaffe, Ronen; Adawi, Salim; Lavi, Idit; Schliamser, Jorge E.; Flugelman, Moshe Y.; Shiran, Avinoam
Abstract: Aims: Over the last four decades, in-hospital mortality from acute coronary syndromes (ACS) has declined. We characterized the patients who died in our cardiovascular intensive care unit (CICU) over a 15-year period. Based on these data, we described the changing patient population in the CICU. Methods: This retrospective study compared characteristics of patients who died in our CICU in 2005–6, 2013–4 and 2019. During these 5 years, 13, 931 patients were hospitalized; 251 (1.8%) died. The mean age of the patients who died was 76 years, 144 (57%) were men. ACS was the leading cause of admission (93 patients, 37%), and 145 (58%) patients had a history of heart failure prior to hospitalization. The leading cause of death was cardiogenic shock in 104 (41%) patients, septic shock in 48 (19%) patients, and combined cardiogenic and septic shock in 31 (12%). Patients hospitalized in the later years of the study were significantly older (67.7, 69.0 and 70.5 years, 2005–6, 2013–4 and 2019, respectively, p < 0.02) but their medical characteristics did not differ significantly between the years examined. Conclusions: The profile of the patients who died did not change significantly over the 15-year study period. Age of admitted patients was higher in later years of the study. The leading cause of admission was ACS and the leading causes of death were cardiogenic and septic shock. Based on our observations, additional skills should be added to the curriculum of cardiology, including the management of patients with multiorgan failure.